Value Investing Paradigm: Driving property management and digital innovation for Optimal Firm Performance in Property Industries - Inthalasari, Rini; Arief, Muhtosim; Hamsal, Mohamad; Abdinagoro, Sri Bramantoro (Journal of Ecohumanism, 2024)
The property and real estate industry plays an important role in a country’s economic progress by creating jobs, encouraging production and maintaining financial stability. The aim of this research is to encourage property management and digital innovation for optimal Company Performance in the Property Industry. This study examines the interplay between Property Management, Digital Innovation, Value Investing, and Firm Performance within the context of the property industry in Indonesia. The research employs a quantitative methodology. Data was gathered through questionnaires distributed to top management individuals from 23 property companies in Indonesia, with a sample size of 254 determined through proportionate stratified random sampling. The analysis was performed using the Partial Least Squares (PLS) method with SmartPLS software. The results highlight Property Management and digital innovation independently contribute to firm performance, underscoring their importance in driving organizational success within the property industry. Mediation analysis reveals value investing’s mediating role between Property Management/digital innovation and firm performance, emphasizing investment decisions’ intermediary function in translating property management efforts and digital innovation initiatives into tangible business outcomes. These findings underscore the significance of integrating effective property management practices, innovative digital strategies, and value-centric investment approaches to enhance firm performance in the dynamic landscape of the property industry.